Effect of various staining beverages on the color stability of CAD/CAM PMMA denture teeth: An in vitro study - Ehab Alouch; Mawia Karkoutly; Omar Teriaky (Wiley, 2024)
Abstract Objective This study aimed to compare the color change of computer‐aided design (CAD)/computer‐aided manufacturing (CAM) polymethyl methacrylate (PMMA) denture teeth and conventional acrylic teeth after immersion in three staining beverages (coffee, red tea, and cola) for a day, 7 days, and 30 days. Materials and Methods Group 1: Conventional acrylic teeth (n = 32). Group 2: Milled CAD/CAM teeth out of PMMA disc (n = 32). The specimens of each material were further divided into four subgroups: (1) Control group, distilled water (n = 16). (2) Red tea solution (n = 16). (3) Coffee solution (n = 16). (4) Cola (n = 16). The color change (∆ E) was assessed using a spectrophotometer at four time points: at the baseline (t0), on the 1st day (t1), on the 7th day (t2), and the 30th day (t3) of immersion. Kolmogorov-Smirnov test was applied, followed by performing independent samples t test, one‐way analysis of variance and post‐hoc Tukey tests to compare the color change values at different time points. Results The mean score of NBS values of the coffee solution indicates perceivable color change at the end of the 30th day in the conventional acrylic teeth group. It was 0.843 ± 0.395 at t1, then increased to 1.017 ± 0.477 at t2 and to 2.259 ± 1.059 at t3. There is a statistically significant difference (p < 0.05) in color change values between both tooth types at the end of the 30th day of immersion in red tea solution and a statistically significant difference at the end of the 7th day (p < 0.05) and the 30th day (p < 0.05) of immersion in coffee solution. Conclusions CAD/CAM PMMA teeth are more color stable than conventional acrylic teeth after 30 days of immersion in coffee and red tea solution.